Integrative analysis of the intestinal metabolome of childhood asthma - Lee-Sarwar, Kathleen A.; Kelly, Rachel S.; Lasky-Su, Jessica; Zeiger, Robert S.; O'Connor, George T.; Sandel, Megan T.; Bacharier, Leonard B.; Beigelman, Avraham; Laranjo, Nancy; Gold, Diane R.; Weiss, Scott T.; Litonjua, Augusto A. (Journal of allergy and clinical immunology, 2019)
The intestinal metabolome reflects the biological consequences of diverse exposures and might provide insight into asthma pathophysiology. We sought to perform an untargeted integrative analysis of the intestinal metabolome of childhood asthma in this ancillary study of the Vitamin D Antenatal Asthma Reduction Trial. Metabolomic profiling was performed by using mass spectrometry on fecal samples collected from 361 three-year-old subjects. Adjusted logistic regression analyses identified metabolites and modules of highly correlated metabolites associated with asthma diagnosis by age 3 years. Sparse canonical correlation analysis identified associations relevant to asthma between the intestinal metabolome and other “omics”: the intestinal microbiome as measured by using 16S rRNA sequencing, the plasma metabolome as measured by using mass spectrometry, and diet as measured by using food frequency questionnaires. Several intestinal metabolites were associated with asthma at age 3 years, including inverse associations between asthma and polyunsaturated fatty acids (adjusted logistic regression β = −6.3; 95% CI, −11.3 to −1.4; P = .01) and other lipids. Asthma-associated intestinal metabolites were significant mediators of the inverse relationship between exclusive breast-feeding for the first 4 months of life and asthma (P for indirect association = .04) and the positive association between a diet rich in meats and asthma (P = .03). Specific intestinal bacterial taxa, including the family Christensenellaceae, and plasma metabolites, including γ-tocopherol/β-tocopherol, were positively associated with asthma and asthma-associated intestinal metabolites. Integrative analyses revealed significant interrelationships between the intestinal metabolome and the intestinal microbiome, plasma metabolome, and diet in association with childhood asthma. These findings require replication in future studies. [Display omitted]